1995
DOI: 10.1073/pnas.92.14.6562
|View full text |Cite
|
Sign up to set email alerts
|

Different cellular backgrounds confer a marked advantage to either mutant or wild-type mitochondrial genomes.

Abstract: After the introduction of mitochondria with a mixture of mutant and wild-type mitochondrial DNA (mtDNA) into a human p0 cell line (143B.206), Yoneda et al. [Yoneda, M., Chomyn, A., Martinuzzi, A., Hurko, 0. & Attardi, G. (1992) Proc. Natl. Acad. Sci. USA 89, [11164][11165][11166][11167][11168] observed a shift in the proportion of the two mitochondrial genotypes in a number of cybrid clones. In every case where a shift was observed, there was an increase in the proportion of mutant mtDNA. By using the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(128 citation statements)
references
References 21 publications
(27 reference statements)
4
121
3
Order By: Relevance
“…Thus, in hybrids and cybrids preferential accumulation might be a property not only of del-mtDNA. A cybrid's nuclear genome may be involved in mtDNA segregation as well, as was clearly demonstrated in relation to the ME-LAS 3243 point mutation (Dunbar et al 1995). Although it is impossible from the present study to determine to what extent the accumulation of del-mtDNA was influenced by its original parental nucleus, the ease with which delmtDNA was selected against suggests a passive role of the nuclear genome.…”
Section: Preferential Accumulation Of Del-mtdnamentioning
confidence: 63%
See 1 more Smart Citation
“…Thus, in hybrids and cybrids preferential accumulation might be a property not only of del-mtDNA. A cybrid's nuclear genome may be involved in mtDNA segregation as well, as was clearly demonstrated in relation to the ME-LAS 3243 point mutation (Dunbar et al 1995). Although it is impossible from the present study to determine to what extent the accumulation of del-mtDNA was influenced by its original parental nucleus, the ease with which delmtDNA was selected against suggests a passive role of the nuclear genome.…”
Section: Preferential Accumulation Of Del-mtdnamentioning
confidence: 63%
“…It has been suggested that not only del-mtDNA but also mtDNA containing a point mutation may accumulate with time, in patients as well as in cell-culture (Yoneda et al 1992;Attardi et al 1995). Nuclear background was shown to influence this behaviour (Dunbar et al 1995), which raises questions regarding the mechanism(s) of the replicative advantage of any mutant mtDNA, including mtDNA molecules of smaller than wild-type size, and its relationship with the phenotypic effects of the mutation.…”
Section: Introductionmentioning
confidence: 99%
“…11 Altogether, these mtDNA deletion in Pearson syndrome JMW van den Ouweland et al y data indicate that segregation of deleted mtDNA may, or may not occur depending on the nuclear background of the cell containing deleted mtDNA. Also, in cybrid cells containing partially duplicated mtDNA 25 or a specific point mutation in the mtDNA at np 3243, 26 uridine and the nuclear background were found as factors influencing the segregation of the mitochondrial phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In an A549 lung carcinoma MELAS cybrid model, a 50 % mutational load results in a 50 % reduction in cytochrome oxidase activity [21]. This illustrates the important role the nuclear genome plays in the mitochondrial genotype-phenotype relationships [22].…”
Section: Application Of Cybrids To Clinical Medicinementioning
confidence: 83%